Spatio-temporal variation in progression rates of black band disease between Pramuka Island and Pari Island of the Seribu Islands, Indonesia - Ofri, Ofri Johan; Ginanjar, Rendy; Rustam, Agustin; Ardi, Idil; Sholichah, Lili; Rachmawati, Rita; Siringoringo, Rikoh Manogar; Abrar, Muhammad; Sari, Ni Wayan Purnama; Giyanto; Samusamu, Andrias Steward; Undap, Nani Ingrid; et al. (Frontiers in Marine Science, 2024)
Black band disease (BBD) is one of the oldest recognized diseases of scleractinian corals. This disease is little known on the variation of progression rates across relatively small spatial scales and how local variations in the environment can impact prevalence and spread. The purpose of this study was to explore the progression of BBD on genus Montipora in relation to spatio-temporal environmental parameters in two islands of the Seribu Islands, North Jakarta, Indonesia during dry season and rainy season. Monthly underwater pictures were taken for determining the progress of disease level. Interestingly, the progression rate of the disease recorded at Pramuka Island was higher (8.10 cm2 day-1) than the one at Pari Island (3.79 cm2 day-1). In Pramuka Island, the infected corals had almost 89% of the dead surface, compared to only 68% at Pari Island. Similar to other studies in the region, we confirmed that the disease progressed faster during the dry season, where the environmental parameters, such as temperature, light intensity, and phosphate, were starting to increase, while total organic matter, current flow rates, and turbidity were lower. Progression of the disease was significantly different between seasons (p<0.001), but not between sites (p=0.118). Therefore, the progress of BBD has a higher impact at the more populated Pramuka island than at the less populated Pari Island, in addition to the influence of environmental parameters on coral vulnerability to diseases.